2022
DOI: 10.1037/dhe0000361
|View full text |Cite
|
Sign up to set email alerts
|

How STEM lab settings influence graduate school socialization and climate for students of color.

Abstract: In this article, we examine how science, technology, engineering, and mathematics (STEM) lab settings influence graduate school socialization and climate for Students of Color. While the literature has highlighted the importance of labs within STEM graduate education and the impediments to success for graduate Students of Color, limited research has explicitly attended to the experiences of graduate Students of Color within their respective labs. Understanding how STEM graduate Students of Color perceive and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 43 publications
(146 reference statements)
1
9
0
Order By: Relevance
“…For example, Stockard et al (2021) examined inequalities in the graduate experiences of underrepresented minorities (URMs) in Chemistry, in which they revealed that URMs are less likely to report insufficient financial support or have supportive relationships with peers and advisors. Likewise, Rodriguez et al (2022) examined the experiences of graduate students of color in STEM research laboratory settings and reported that graduate students of color characterized their socialization experiences in their STEM labs as both isolating and competitive, disruptive to their familial structures, and forcing them to create their own structures of support. Although these studies and others (e.g., Bahnson et al, 2019; Fisher et al, 2019; Wilkins‐Yel et al, 2019) provide necessary evidence of systemic inequalities related to race/ethnicity in graduate science experiences, they overlook racialized experiences that emerge from careful consideration for the heterogeneity of the race and ethnic groups that make up the social construct of students of color or underrepresented minorities and they ignore the unique contexts of certain scientific disciplines.…”
Section: Empirical Underpinningsmentioning
confidence: 99%
“…For example, Stockard et al (2021) examined inequalities in the graduate experiences of underrepresented minorities (URMs) in Chemistry, in which they revealed that URMs are less likely to report insufficient financial support or have supportive relationships with peers and advisors. Likewise, Rodriguez et al (2022) examined the experiences of graduate students of color in STEM research laboratory settings and reported that graduate students of color characterized their socialization experiences in their STEM labs as both isolating and competitive, disruptive to their familial structures, and forcing them to create their own structures of support. Although these studies and others (e.g., Bahnson et al, 2019; Fisher et al, 2019; Wilkins‐Yel et al, 2019) provide necessary evidence of systemic inequalities related to race/ethnicity in graduate science experiences, they overlook racialized experiences that emerge from careful consideration for the heterogeneity of the race and ethnic groups that make up the social construct of students of color or underrepresented minorities and they ignore the unique contexts of certain scientific disciplines.…”
Section: Empirical Underpinningsmentioning
confidence: 99%
“…A positive experience in graduate school can be seen largely as the result of socialisation – a process in which students develop their professional identity 5 through gaining “knowledge, skills, and values necessary for successful entry into a professional career” 3 . Higher education research shows that differences in socialisation often align with differences in race, gender, and other socioeconomic factors 1 , 6 …”
Section: The Case For Actionmentioning
confidence: 99%
“…The success in changing the source data for the global primary care ranking and its weight is a step in the right direction, but the greater success was in adding 4 new rankings in 2021 (2022 rankings): (1) graduates practicing in primary care fields; (2) student diversity; (3) graduates practicing in medically underserved areas; and (4) graduates practicing in rural areas. The methods underpinning the new additional rankings are explained in US News . These changes reflect a long collaboration between the Robert Graham Center of the American Academy of Family Physicians and the Fitzhugh Mullan Institute at George Washington University (Washington, DC) to develop social mission measures for medical schools …”
Section: New Measures For Primary Care Rankingsmentioning
confidence: 99%